2019
DOI: 10.1017/s1751731119000776
|View full text |Cite
|
Sign up to set email alerts
|

Protein restriction and succedent realimentation affecting ileal morphology, ileal microbial composition and metabolites in weaned piglets

Abstract: Dietary protein restriction is one of the effective ways to reduce post-weaning diarrhoea and intestinal fermentation in piglets, but it may also reduce growth performance. The compensatory growth induced by subsequent protein realimentation may solve the issue. However, little research has been done on the impact of protein realimentation on the gut. In this study, the effects of protein restriction and realimentation on ileal morphology, ileal microbial composition and metabolites in weaned piglets were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Thus, understanding the microbiota composition of rats with HEinduced ECD may help formulate microbial intervention strategies. Recent studies have focused on the effects of HE on the intestinal and fecal microbiota of economic animals, such as chickens, pigs, cows, buffalos, and so on (Chen et al, 2018;He et al, 2019;Shi et al, 2019;Zhu et al, 2019). They have promoted a comprehensive analysis of the vaginal microbiota of rats with HE-induced ECD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, understanding the microbiota composition of rats with HEinduced ECD may help formulate microbial intervention strategies. Recent studies have focused on the effects of HE on the intestinal and fecal microbiota of economic animals, such as chickens, pigs, cows, buffalos, and so on (Chen et al, 2018;He et al, 2019;Shi et al, 2019;Zhu et al, 2019). They have promoted a comprehensive analysis of the vaginal microbiota of rats with HE-induced ECD.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate lowering of the dietary protein concentration also improved the α-diversity of that intestinal microbial community in growing pigs ( Peng et al, 2017 ; Chen X. et al, 2018 ). However, an excessive protein decrease, i.e., a very low protein intake, was detrimental to the microbiota structure ( Shi et al, 2019 ; Spring et al, 2020 ). Therefore, changes in microbiota upon dietary protein in pigs are dose- and site-dependent ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clostridium_sensu_stricto_1 is usually considered as pathogenic bacteria as well as an indicator of a less healthy microbiota [56,57]. It has been reported that the enrichment of Clostridium_sensu_stricto_1 was associated with the high transcript levels of proin ammatory cytokines in the sheep colon, impaired intestinal barrier function in pigs and necrotizing enterocolitis in preterm infants [58][59][60]. As a result, the decrease in the abundance of Clostridium_sensu_stricto_1 may be an indicator of a healthy microbiota and a contributor to the reduced concentrations of in ammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%